PENGARUH CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN KEPEMILIKAN MAYORITAS TERHADAP AGRESIVITAS PAJAK - Puput Putrianika (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
This study aims to examine the effect of corporate governance (CG), corporate social responsibility (CSR), and majority ownership on corporate tax aggressiveness. The method used is descriptive with a quantitative approach. The data used in this research is secondary data obtained from www.idx.co.id and IICG. Data were analyzed using multiple regression with SPSS 22.0 software. The research sample was taken using purposive sampling method. The sample of this study used 9 companies that were included in the CGPI ranking during the years 2012-2015. The results showed that corporate governance and majority ownership had no effect on tax aggressiveness. Meanwhile, corporate social responsibility has a significant negative effect on tax aggressiveness. For further research, it is expected to use other variables that can influence tax aggressiveness and to use other proxies to measure the level of tax aggressiveness.